Pengaruh KompetenPengaruh Kompetensi dan Motivasi Pengurus terhadap Kinerja Badan Usaha Milik Desa (BUMDes) Niut Rayasi dan Motivasi Pengurus terhadap Kinerja Badan Usaha Milik Desa (BUMDes) Niut Raya - Trisnanti, Risma; Yurisinthae, Erlinda; Aritonang, Marisi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
BUMDes is one of the business entities that can be an alternative for village communities in developing and utilizing existing potential by optimizing human resources in managing them. low competence and motivation are the background to problems related to lack of human resources and less than optimal performance. This research aims to analyze the influence of management competency and motivation on the performance of Niut Raya Village-Owned Enterprises (BUMDes) management. The research was conducted in Pisak Village, Seventeen District, Bengkayang Regency with 10 respondents consisting of BUMDes administrators. This research uses population research which uses the entire population as a sample. The method used is quantitative descriptive. Data analysis techniques use validity testing, reliability testing, classical assumption testing, model feasibility testing and hypothesis testing using the SPSS 23.0 tool. The feature that will be used in this version is bootstrapping. The research results show that management competency does not influence the performance of BUMDes management. However, there are several suggestions that researchers put forward, namely creating clear guidelines on managing BUMDes finances and assets, implementing a financial information system that makes it easier to record, reporting and analyzing BUMDes finances, carrying out local potential analysis to identify all the resources available in the village and develop strategic plan to exploit local potential. Management motivation influences the performance of BUMDes management. The suggestions put forward are providing training, providing appropriate salaries, giving prizes to administrators who have good performance, creating a comfortable working atmosphere and good cooperation between administrators.